Three new genera of Schizopteridae from Australia with description of six new species (Hemiptera: Heteroptera: Schizopteridae) - Hill, Lionel (Zootaxa, 2015)
From Australia, three new schizopterid genera are described for six new species. The three new genera and Pachyplagioides Gross, 1951 share a declivent head with well-developed internal postocciptal region and a 3-segmented labium with bulbous base. The new genera and species are Parvodeceptor infrequens gen. n., sp. n., Dextritubus cucullatus gen. n., sp. n., D. acucullatus gen. n., sp. n., D. nubis gen. n., sp. n., Carinatala septentrionalis gen. n., sp. n. and C. meridiana gen. n., sp. n. Their description brings to near completion the known generic diversity of Australian Schizopteridae. Parvodeceptor has superficially hypselsomatine facies and may have affinity with the African Humpatanannus Wygodzinsky 1950. Dextritubus has accessory male genitalia reminiscent of Semangananus Stys, 1974 and Vilhenannus Wygodzinsky, 1950. Carinatala has dentate male fore and mid claws, not previously recorded in the family, and an unusual inflatable, spiculate vesica reminiscent of Dundonannus Wygodzinsky 1950. The retention of the internal postocciptal region in several schizopterid genera and lack of its correlation with declivent versus porrect head condition is outlined.